Lower Serum Catalase Level is Associated with Preterm Labor among Pregnant Women at Sanglah Hospital Denpasar, Bali-Indonesia - Negara, I Ketut Surya; Surya, IGP; Sanjaya, Hariyasa; Anantasika, AAN; Mahardika, I Made (BALI MEDICAL JOURNAL, 2016)
Background: Preterm labor is still become a serious health problem in Obstetric and Perinatology with no sensitive biomarker currently approved. Several studies show that decrease antioxidant activity may play significant role in preterm labor. However, only few studies had been conducted to evaluate blood catalase level in preterm labor and assess its role in preterm labor. Objective: The aim this study was to identify the differences of maternal serum catalase level in preterm labor compared with preterm pregnancy. Methods: An observational analytic cross sectional study was conducted from February to December 2014 using pregnant women with 28-36 weeks’ gestational age. Blood catalase level was evaluated by colorimetric method and the data was analyzed by SPPS for Windows 17.0 program. Results: 12 subjects were enrolled and divided into preterm and control group. No significant differences between mean age, gestational age, and parity between preterm and control group. However, blood catalase level was significantly lower in preterm group compared with control group (81.82 ± 20.38 vs 159.38 ± 35.79; p=0.001). Conclusion: Serum maternal catalase level were significantly lower in preterm labor compared with preterm normal pregnancy.